2021
DOI: 10.7150/thno.50741
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell-derived exosomes endowed with VEGF plasmids enhance osteogenic induction and vascular remodeling in large segmental bone defects

Abstract: Large segmental bone regeneration remains a great challenge due to the lack of vascularization in newly formed bone. Conventional strategies primarily combine bone scaffolds with seed cells and growth factors to modulate osteogenesis and angiogenesis. Nevertheless, cell-based therapies have some intrinsic issues regarding immunogenicity, tumorigenesis, bioactivity and off-the-shelf transplantation. Exosomes are nano-sized (50-200 nm) extracellular vesicles with a complex composition of proteins, nucleic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 49 publications
0
120
0
7
Order By: Relevance
“…However, to fully understand the possibilities of exosomes as cancer treatments, more research is needed. Exosomes generated by stem cells have also been effectively utilized to promote osteogenesis in vivo, allowing for both development of new blood vessels and the formation of bone [ 227 , 229 ].…”
Section: Critical Discussion and Perspectivementioning
confidence: 99%
“…However, to fully understand the possibilities of exosomes as cancer treatments, more research is needed. Exosomes generated by stem cells have also been effectively utilized to promote osteogenesis in vivo, allowing for both development of new blood vessels and the formation of bone [ 227 , 229 ].…”
Section: Critical Discussion and Perspectivementioning
confidence: 99%
“…It is known that HIF-1α and VEGF is an effective factor to improve the scaffold vascularization via angiogenesis [15,49]. The levels of angiogenesis-related gene, HIF-1α, was increased signi cantly in the EPC/hTi Group compared with eTi Group, hTi Group, and BMSC/hTi Group (p < 0.05).…”
Section: Angiogenesis-and Osteogenesis-related Gene Expression In Bonementioning
confidence: 99%
“…In addition, a series of surface modi cation strategies have also been used to induce osteogenesis and osseointegration of the porous titanium scaffolds [12,13]. Although it is recognized that the use of additional BMSC incorporation or prosthetic surface modi cation to treat bone defects can effectively accelerate bone formation, the size of the regenerated bone has always been a restriction for su cient bone repair, mainly because of the absence of blood vessels in the grafts [14,15]. Since abundant angiogenesis is critical to provide su cient nutritional support, active osteoblast function, and accelerate new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…59 Recent research has shown that modified exosomes combined with a 3D printed porous bone scaffold through a specific linker (exosomal anchor peptide CP05) can effectively increase the osteogenesis and angiogenesis by exosomes encapsulating the VEGF gene. 60…”
Section: D Bioprinted Scaffoldsmentioning
confidence: 99%